The Persistence of Multifamily Firms: Founder Imprinting, Simple Rules, and Monitoring Processes. (30th July 2015) - Pieper, Torsten M.; Smith, Anne D.; Kudlats, Jerry; Astrachan, Joseph H.
<x xml:space="preserve">Abstract</x> This study focuses on a particular form of family businesses—businesses with at least two unrelated founding families—and how their organizational form of a multifamily business persists over several generations. Using an inductive approach to study five multifamily cases, we discovered that these firms did not meet complexity with complex structures and processes. Instead, four cases developed and utilized simple rules imprinted by the founders and pulled through to current generations, enabling effective mutual monitoring and persistence of the multifamily organizational form. The lack of simple rules development is associated with one multifamily business to abandon this organizational form.